The Concept of Taʿzir in Fiqh Jinayat and Its Relevance to Traffic Ticket Sanctions in Indonesian Traffic Law - Adnan, Mohammad; Uyuni, Badra; Saleh, Muhammad; Siagian, Nilasari; Judijanto, Loso (AL-ISTINBATH : Jurnal Hukum Islam, 2025)
This study aims to examine traffic ticket sanctions from the perspective of fiqh jinayat, with a particular focus on the concept of ta'zir as a form of punishment that is flexible and delegated to the discretion of the ruling authority (ulil amri). In the context of traffic law in Indonesia, traffic fines are implemented to enforce order and reduce violations that may endanger public safety. This study focuses on how fiqh jinayat provides a normative foundation for the enforcement of traffic sanctions and its relevance within Indonesia’s positive legal system. This study uses a qualitative normative-sociological approach to examine how taʿzir-based traffic sanctions shape public legal awareness and influence community compliance with traffic regulations. The analysis uses an explanatory method to explore the correlation between the principles of ta'zir and modern traffic law policy. The findings demonstrate that fiqh jinayat positions traffic sanctions within the framework of maslahah, aiming to protect life (hifzh al-nafs) and property (hifzh al-mal). Traffic ticket penalties in Indonesia, such as fines for not wearing helmets, license suspensions for reckless driving, or vehicle impoundment for driving without valid documents, can be classified as taʿzīr punishments. These sanctions function preventively by deterring future violations and repressively by disciplining offenders to maintain social order. This study affirms that the principles of fiqh jināyāt, particularly the concept of taʿzīr, can serve as an ethical and normative foundation for enforcing traffic ticket sanctions within Indonesia’s positive legal system. Such integration is essential for strengthening justice, promoting road safety, and ensuring collective welfare in Indonesian society. This study contributes to the development of contextual Islamic law, particularly through the integration of maqāṣid al-sharīʿah values with the modern legal system to strengthen public compliance with regulatory norms.